2017
DOI: 10.1002/2016wr018878
|View full text |Cite
|
Sign up to set email alerts
|

Estimating snow water equivalent in a Sierra Nevada watershed via spaceborne radiance data assimilation

Abstract: This paper demonstrates improved retrieval of snow water equivalent (SWE) from spaceborne passive microwave measurements for the sparsely forested Upper Kern watershed (511 km2) in the southern Sierra Nevada (USA). This is accomplished by assimilating AMSR‐E 36.5 GHz measurements into model predictions of SWE at 90 m spatial resolution using the Ensemble Batch Smoother (EnBS) data assimilation framework. For each water year (WY) from 2003 to 2008, SWE was estimated for the accumulation season (1 October to 1 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 104 publications
(155 reference statements)
0
30
0
Order By: Relevance
“…In terms of space‐borne radiance data assimilation, Andreadis and Lettenmaier () showed that assimilating SSM/I observations into a one‐layer model had no impact on snow depth estimates but that assimilating these observations into a multilayer snow model can dramatically improve the model predictability. Similarly encouraging performance in snow mass estimation was also witnessed during the snow accumulation season via assimilation of AMSR‐E Tb observations in Siberia (Che et al, ) and in the Sierra Nevada (Li et al, ). In terms of continental‐scale estimates, Kwon et al () assimilated vertically polarized AMSR‐E Tb observations at 18.7 and 36.5 GHz over North America from December 2002 to February 2003 and found modest improvements in snow depth across regions of tundra (as defined in Sturm et al, ) and bare soil cover (as defined in the Community Land Model Version 4 for land without vegetation).…”
Section: Introductionmentioning
confidence: 64%
“…In terms of space‐borne radiance data assimilation, Andreadis and Lettenmaier () showed that assimilating SSM/I observations into a one‐layer model had no impact on snow depth estimates but that assimilating these observations into a multilayer snow model can dramatically improve the model predictability. Similarly encouraging performance in snow mass estimation was also witnessed during the snow accumulation season via assimilation of AMSR‐E Tb observations in Siberia (Che et al, ) and in the Sierra Nevada (Li et al, ). In terms of continental‐scale estimates, Kwon et al () assimilated vertically polarized AMSR‐E Tb observations at 18.7 and 36.5 GHz over North America from December 2002 to February 2003 and found modest improvements in snow depth across regions of tundra (as defined in Sturm et al, ) and bare soil cover (as defined in the Community Land Model Version 4 for land without vegetation).…”
Section: Introductionmentioning
confidence: 64%
“…However, GRACE TWS retrievals feature a very coarse resolution (around 100 km) so that they would only be useful in conjunction with fSCA retrievals for very large scale applications. On the other hand, the use of higher-resolution PM SWE retrievals (order 25 km) in the assimilation has shown particular promise (e.g., De Lannoy et al, 2012;Li et al, 2017). At the same time, PM SWE retrievals are not accurate in complex topography and forested areas, nor for wet and deep snowpacks (Foster et al, 2005), which might limit the applicability of such multisensor assimilation approaches.…”
Section: Discussionmentioning
confidence: 99%
“…This was extended to a real multisensor experiment by jointly assimilating PM SWE and MODIS fSCA retrievals (De Lannoy et al, 2012). Li et al (2017) used the ES to assimilate PM SWE retrievals and estimate the SWE distribution, markedly outperforming the OL. Of late, particle filter (PF; see Van Leeuwen, 2009) schemes have been gaining popularity in snow DA studies (Charrois et al, 2016;Magnusson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of snow (in particular its water equivalent [SWE]), it remains relatively poorly characterized, especially in mountainous regions where both high values of SWE and its spatial variability simultaneously exist. In a recent survey of the state of hydrologic remote sensing, Lettenmaier et al () concluded that SWE is the variable “that is most in need of new strategic thinking from the hydrologic community.” They note that while efforts to develop estimates of SWE using passive microwave sensors go back almost four decades, large‐scale applications of those methods are hampered by extreme complications in forested and topographically complex environments with deep snow (Cai et al, ), or for snowpacks containing substantial liquid water (Li, Durand, & Margulis, ). The need for snow estimates is echoed in the recently published National Academies Decadal Review of Earth Science and Applications from Space (i.e., “Decadal Survey”; National Academies of Sciences, Engineering, and Medicine, ), which classified among its “most important” level of objectives to “Quantify rates of snow accumulation, snowmelt, ice melt, and sublimation from snow and ice worldwide at scales driven by topographic variability.”…”
Section: Introductionmentioning
confidence: 99%